Vitamins and your health - Gamez, Cisco; Mann, Blaine; Educational Video Network (Huntsville, TX: Educational Video Network)
Explaines how vitamins affect human bodies and where people can find these important vitamines so that they may be healthy
Videography, Cisco Gamez, Christina Vuckovic ; editor, Cisco Gamez
Host: Blaine Mann ; narrator, Thomas F. Soare
Keywords: Vitamins; Dietry supplements